(untitled) (Revista Brasileira Multidisciplinar, 2023)
Streptococcus agalactiae is part of the human microbiota, residing in the genitourinary and gastrointestinal tracts, however, due to the weakening of the immune system, this microorganism can proliferate and cause symptoms. S. agalactiae is the main cause of disease in newborns, with the immune system still in formation, babies can acquire the bacterial infection through normal delivery when the baby is passing through the mother’s vagina, the region in which S. agalactiae. They are sensitive microorganisms, but they have resistance mechanisms which try to circumvent the immune system. The immune system is made up of a complex network of cells and molecules that act in the body’s defense. Neutrophils, which are part of the first line of defense, have an effective intracellular machinery in the destruction of pathogens, however, this fight can be complex, requiring the help of an antimicrobial. Given this context, the objective of this study was to evaluate the functions of neutrophils in the presence of Streptococcus agalactiae under the effect of the most used antimicrobial in infections against this microorganism, Penicillin. To carry out this work, laboratory practices were used that included the cell viability test of neutrophils at different doses of Penicillin by Trypan blue; evaluation of neutrophil phagocytic activity; evaluation of the bactericidal function of the neutrophil and bacterial viability test. The results showed that the cell viability of neutrophils did not show relevant changes, the concentrations of Penicillin used to inhibit the growth of the bacteria did not harm the structure of neutrophils, as well as their functions; the antimicrobial did not interfere in the phagocytic activity of the neutrophil either. The presence of the antibiotic did not inhibit bacterial growth and the bactericidal activity of the neutrophil was ineffective, which presupposes that the bacterial virulence factors influenced this result.